Ensuring equity for people living with disabilities in the age of COVID-19. Issue 10 (21st August 2020) - Jumreornvong, Oranicha; Tabacof, Laura; Cortes, Mar; Tosto, Jenna; Kellner, Christopher P.; Herrera, Joseph E.; Putrino, David
Abstract: People with disabilities are at higher risk of severe illness from COVID-19. They may also suffer from lack of accessible emergency preparedness plans, communication and healthcare. Protective measures for people with disabilities should be endorsed and prioritized at a community level to adjust for social distancing. Repositories of local resources for emergency outreach in this time are also crucial. Telemedicine offers an innovative and safe way for health providers to care for people with disabilities to access many critical services without placing themselves or their caregivers at increased risk of contracting COVID-19. Communication strategies for critical information about resources for people with disabilities should be accessible. United States hospitals and government agencies should make allocation guideline proposals accessible to people with disabilities and incorporate bias training.